Reforming the international financial architecture: what globalization critics demand and what policymakers have (not) achieved - Peter Nunnenkamp (Journal of financial transformation, 2003)
The frequency and severity of financial and currency crises in emerging market economies since the mid-1990s have increasingly eroded confidence in the well-functioning of international capital markets. Cross-border currency transactions recorded a spectacular growth, reaching US 1500 billion per day in the late 1990s or about two thirds of Germany's annual GDP. About 80 percent of these transactions involve round-trips of seven days or less. Globalization critics conclude that international financial transactions have little to do with real economic activity, such as foreign trade, and are predominantly speculative in nature. In order to tame speculation and protect emerging market economies from the vagaries of global financial markets, globalization critics demand radical changes in the international financial order. Policymakers, notably those in major industrial countries, are criticized for remaining committed to liberalized financial markets. However, a fundamental reconstruction of the financial architecture does not only lack political support. As argued below, some radical reform proposals are also flawed from an economic point of view. Yet policymakers are to be blamed for having delivered at best partly what they had promised after recent financial crises, namely to adjust the regulatory framework to increased global capital mobility. In important respects, the process of reforming the international financial architecture appears to be stalled, mainly because of conflicting interests of major political players.
Keywords: 330; Internationales Währungssystem; Internationaler Finanzmarkt; Entwicklungsbank; Reform